PENGARUH PEMBIAYAAN DAN KAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY MELALUI LABA SEBAGAI VARIABEL INTERVENING PADA BANK UMUM SYARIAH DI INDONESIA - Ahmad Roziq; Ibnu Aburizal N MS (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
Corporate social responsibility is neccessity to every corporate. Islamic banking is requirement every shariah bank to doing social services in human resource development and contribution donation with care and maintenance environment. The basic of shariah bank can be exist in UU.No.21 Tahun 2008 Pasal 4. The kind of this research is explanatory research. This research have four variable, that is financing (X1), cash (X2), profit (Y1) and corporate social responsibility (Y2). The populations in this research is an shariah bank listed in Bank of Indonesia until year of 2010. That hipotesys examination have path analyzis with Partial Least Square. The yield research can know that endogen variable have a significant influences to exsogen variable. Authentification this research with values of t-value is more bigger than t-tabel. The details is financing (X1) to profit (Y1) with value of 5,136>1,734 ; cash (X2) to profit (Y1) with value of 2,237>1,734; financing (X1) to corporate social responsibility (Y2) with value of 3,031>1,734 ; profit (Y1) to corporate social responsibility (Y2)with value of 4,053>1,734 and cash (X2) to corporate social responsibility (Y2) with value of 3,052>1,734. Value of R-square is 0,758 in first equation and 0,626 in second equation. Keyword : financing, cash, profit, corporate social responsibility, shariah bank,